Simons type formulas for surfaces in Sol3 and applications - Dorel Fetcu (Bulletin of Mathematical Sciences, 2023)
We compute the Laplacian of the squared norm of the second fundamental form of a surface in Sol3 and then use this Simons type formula to obtain some gap results for compact constant mean curvature surfaces of this space.